RISK FACTORS OF NEW CARIES BASED ON CHILD DENTAL CARIES PREDICTOR APPROACH: FAKTOR RESIKO KARIES BARU BERDASARKAN PENDEKATAN PREDIKTOR KARIES GIGI ANAK - Julita Hendrartini; Supartinah Santoso; Diyah Fatmasari; Quroti A’yun (Dentika: Dental Journal, 2014)
Caries risk factors are factors relate to caries occurrence in individual or population. Caries risk factors vary in everyindividual. A new method to discover the relation between risk factors and caries in children is a software named childdental caries predictor This research aimed to know the general overview of the order of caries risk factor in elementaryschool students in the province of Daerah Istimewa Yogyakarta. This was an observational research with cross-sectionaldesign. The subjects were 430 children, ranging from 10 to 12 years of age. Caries risk factors that were assessed throughchild dental caries predictor were oral and dental condition, mothers and children’s behavior in maintaining dental health,and school environment. The research result showed that the percentage for each risk factor was 39.74% for oral anddental condition, 35.77% for children’s behavior in maintaining dental health, 15.90% for mothers’ behavior inmaintaining child’s dental health, and 7.95% for school environment. In conclusion, the order of children caries riskfactors through measurement using child dental caries predictor are oral and dental condition, children’s behavior inmaintaining dental health, mothers’ behavior maintaining child’s dental health,, and school environment.